2013
DOI: 10.1021/pr400657k
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Alters B-Cell Protein Phosphorylation Profiles

Abstract: Environmental exposure to mercury is suggested to contribute to human immune dysfunction. To shed light on the mechanism we identified changes in the phosphoproteomic profile of the WEHI-231 B cell line after intoxication with Hg2+. These changes were compared to changes in the phosphoproteome that were induced by pervanadate or okadaic acid exposure. Both 250 μM HgCl2 and pervanadate, a known phosphotyrosine phosphatase inhibitor, caused an increase in the number of proteins identified after TiO2 affinity sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…WEHI-231 cells are a well characterized mouse B cell line that exhibits many of the characteristics of immature B cells (Jakway et al , 1986). Our initial experiments utilized qualitative mass spectroscopic techniques to delineate global effects of mercury exposures on the WEHI-231 phosphoproteome, so as to identify potential protein targets of Hg 2+ (Caruthers et al , 2013). In the present study, bioinformatic data analysis algorithms identified the Src family protein phosphokinase Lyn as the “key node” and the B cell receptor signaling pathway as the primary pathway modulated by Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…WEHI-231 cells are a well characterized mouse B cell line that exhibits many of the characteristics of immature B cells (Jakway et al , 1986). Our initial experiments utilized qualitative mass spectroscopic techniques to delineate global effects of mercury exposures on the WEHI-231 phosphoproteome, so as to identify potential protein targets of Hg 2+ (Caruthers et al , 2013). In the present study, bioinformatic data analysis algorithms identified the Src family protein phosphokinase Lyn as the “key node” and the B cell receptor signaling pathway as the primary pathway modulated by Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Y342/Y346 cluster is phosphorylated by LYN leading to binding of Vav-1 and PLC-γ with an affinity that is dependent upon whether the sites are individually or dually phosphorylated [3638]. Previously we have shown that 5 μM Hg does not affect PLC-γ phosphorylation [31], and its not until a very high concentration (250 μM) that we observe an increase [39]. However, low doses of Hg can affect the temporal dynamics of BCR signalosome formation and may alter signaling by outcomes that are yet to be determined.…”
Section: Discussionmentioning
confidence: 92%
“…An additional sample treated with 25 µM pervanadate for 15 min was also prepared to improve our ability to detect phosphotyrosine (pTyr). Pervanadate treatment can result in an accumulation of pTyr to up to 20% of phosphorylated residues (Caruthers et al, 2014). We reasoned that the inclusion of a pTyr enriched sample would improve our ability to detect pTyr residues in data-dependent LC-MS3 analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The expanding capabilities of mass spectrometry based phosphoproteomics in terms of depth of coverage and sample multiplexing (Erickson et al, 2015; Sharma et al, 2014), are making it a powerful systems-level approach for mechanism of action studies. It has already been applied to mechanism of action determination for inorganic mercury (Caruso et al, 2014; Caruthers et al, 2014), deoxyvinylinol (Pan et al, 2013), ammonia (Harder et al, 2014), and to identify the target profiles of kinase inhibitors (Li et al, 2010; Pan et al, 2009). It has emerged from these studies and from other investigations of compounds with known mechanisms (Pines et al, 2011) that the phosphoproteome can provide a more precise determination of mechanism of action than transcriptome or total proteome analysis.…”
Section: Introductionmentioning
confidence: 99%